PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN SALURAN DISTRIBUSI TERHADAP KEPUASAN KONSUMEN KARTU LOOP PADA SISWA SMA DI KOTA SEMARANG - Ardianto Nugroho, 14.05.51.0258; Sholiha, Euis (Students' Journal of Economic and Management, 2018)
This study aims to determine the effect of product quality, price perceptions, and channel distribution to the satisfaction of Loop’s customer. The population in this study are all costumers who use Loop’s sim card that studied in Senior high school in Semarang. Sampling using purposive sampling technique and the number of samples processed into research data as much as 123 respondents. Data were analyzed by using multiple linear regression model. Based on the results of research that has been done shows the quality of products and channel distribution have no effect on costumer’s satisfaction. While the perception of price has significant effect on customer’s satisfaction.Keywords: Product Quality, Price Perception, Channel Distribution and Customer Satisfaction